The effect of various design codes and dynamic magnification on buildings with torsional irregularity - Kwang-Ho Lee (Journal of Vibroengineering, 2016)
Seismic provisions have utilized design eccentricities to reduce planar irregularities in lateral stiffness of buildings. In calculating a design eccentricity, the torsional amplification factor may be applied either to accidental eccentricity or to both inherent and accidental eccentricities according to design codes. In this paper, different code provisions and their impact on torsional responses of buildings are investigated using example buildings with various aspect ratios and inherent eccentricities. It was found that the design eccentricity in KBC-2009 using torsional amplification factor for only accidental eccentricity reflects the dynamic magnification more accurately than that in KBC-2006 using this factor for both inherent and accidental eccentricity. And dynamic magnification of a torsionally imbalanced building is affected by the size of seismic design force of response spectrum analysis than design eccentricity of equivalent static analysis in KBC-2009. In other words, design eccentricity including torsional amplification factor in KBC-2009 do not reflect the dynamic magnification accurately.